Factors that predict severity of infection and seroconversion in immunocompromised children and adolescents with COVID-19 infection - Abu Shanap, Mayada; Sughayer, Maher; Alsmadi, Osama; Elzayat, Ismail; Al-Nuirat, Abeer; Tbakhi, Abdelghani; Sultan, Iyad (Frontiers in Immunology, 2022)
Objectives: We aimed to study the outcomes, severity, and seroconversion post SARS-CoV-2 infection in immunocompromised children and adolescents treated at our center. Method: For this observational study, all pediatric patients who had COVID-19 infection from Sep-22-2020 to Nov-10-2021were identified by reviewing our laboratory records. Their charts were reviewed to determine clinical severity and outcome. Blood samples were drawn for anti-SARS-CoV-2 antibody assay. Serious COVID-19 infection (SVI) was defined if the patient had moderate, severe, or critical illness. A cutoff of 100 U/mL anti-SARS-CoV-2 antibodies was used to categorize low and high titer seroconversion. Results: We identified 263 pediatric patients with COVID-19; most (68%) were symptomatic: 5% had severe or critical infection, 25% were hospitalized, 12 required respiratory support, 12 were admitted to the ICU, and five patients (2 %) died. Multivariable analysis revealed several factors that predict SVI: Age above 12 years (p=0.035), body mass index above 95th percentile (p=0.034), comorbid conditions (p=0.025), absolute neutrophil count ≤500(p=0.014) and absolute lymphocyte count ≤300 (p=0.022). Levels of anti-SARS-CoV-2 spike antibodies were obtained for 173 patients at a median of 94 days (range, 14–300) after PCR diagnosis; of them 142 (82%) patients seroconverted; the lowest seroconversion rate was observed in patients with hematological malignancies (79%). Our univariable model showed that the following factors were predictive of low titer: lower ANC, p=0.01; hematologic malignancy, p=0.023; receiving steroids in the last 14 days, p=0.032; time since last chemotherapy or immunosuppressive therapy less than 30 days, p=0.002; and being on active chemotherapy in the last 3 months prior to infection, p<0.001. Conclusions: SARS-CoV-2 antibodies developed in most immunocompromised patients with COVID-19 infection in our study. Mortality was relatively low in our patients. Our univariable and multivariable models showed multiple variables that predict severity of infections and antibody response post COVID-19 infection. These observations may guide choice of active therapy during infection and the best timing of vaccination in this high-risk population.